Development of Medical Images in Differentiating Benign from Malignant Thyroid Nodules - Luo, Wen; Zhang, Yunfei; Zhou, Xiaodong (Current Medical Imaging, 2016)
As the increasing incidence of thyroid nodules has been recently reported, differential diagnosis between malignancy and benign nodules plays a critical role for determination of therapy plans, but is still a challenge for clinicians. Because of uncertain results of fine needle aspiration (FNA) cytology in some cases, medical images give great noninvasive contribution to differential diagnosis of thyroid nodules. This review of current literature focused on the development of various image modalities on thyroid nodules, in order to supply essentials to clinicians for making pretreatment determination. When ultrasonography is recognized as a routine tool for detecting and differentiating thyroid nodules, improved accuracy has been found when it is combined with FNA. The newly-developed modalities of elastography and contrast enhanced ultrasonography could be used for evaluating the nodule stiffness and vascularity, respectively. Although not recommended as the first-line tool in the managment guideline, scintigraphy supplies supplementary information of the indeterminate nodules after FNA, especially in follicular thyroid nodules. Computed tomography( CT)-detected calcification and its patterns have been regarded to be important sign related to malignancy. Apparent diffusion coefficient ratios on diffusion-weighted magnetic resonance image( MRI) are detected significantly lower in malignant nodules than those in benign ones. CT and MRI are also preferred to demonstrating the surrounding anatomic structures and lymph nodes. The role of PET and PET/CT in the assessment of nodules has been increased, while SUVmax is attractive with a cutoff value about 6.0. In conclusion, with their respective functions, the medical image modalities could supply much helpful information for differential diagnosis of thyroid nodules.
Keywords: thyroid nodule